Chronic Nodular Pulmonary Aspergillosis in a Patient with Rheumatoid Arthritis - Ito, Yuhei (Intern Med, 2019)
Chronic pulmonary aspergillosis, which features nodular lesions known as Aspergillus nodules, is a relatively uncommon disorder. We herein report a case of slowly progressing chronic multiple nodular pulmonary aspergillosis in a 59-year-old man with rheumatoid arthritis, dyspnea, and fatigue. One nodule was surgically resected. The surgical specimen featured central necrosis and was located adjacent to a respiratory bronchiole and pulmonary artery, without parenchymal invasion. Branching septate hyphae, compatible with Aspergillus, were seen inside this necrotic nodule. Chronic pulmonary aspergillosis should therefore be considered in the differential diagnosis of patients who present with slowly progressing pulmonary multiple nodules.